Efecto de inductores de resistencia en el cultivo de pepino, en la ESPAM MFL - Villacreces Loor, Alan Joao (2022)
Resistance inducers are substances that induce physiological changes in plants, activating their defense mechanism, and can be induced by physical or chemical agents. The objective of the research work was to evaluate the effect of resistance inducers on cucumber virus and crop yield. The experiment was carried out in the organic area of the agricultural engineering career of ESPAM MFL, using a completely randomized block design (DBCA), with 5 treatments, 4 replicates and 20 experimental units. The incidence of virosis, fruit length, fruit diameter and fruit weight were determined, as well as the complementary variables of the different treatments. The results obtained in the statistical variables incidence of virosis, length of fruits and diameter of fruits did not show significant differences. On the other hand, in the analysis of variance carried out on the fruit weight variable (g), it showed significant differences (p≤0.05), where the treatment T4 (potassium phosphite) and T1 (acetylsalicylic acid) reached the highest fruit weight with 413,72 and 400,93 g, respectively.